Analisis Pengaruh Kreativitas Produk, Variasi Produk, dan Media Sosial Terhadap Keputusan Pembelian Pada Anna Cake N Cookies di Surabaya - Nafisa, Rizqiya; Nasution, Ute Chairuz M.; Mulyati, Awin (Research Journal of Social Science and Economics, 2025)
UKM (Business, Small and Medium Enterprises) is a business carried out by the community. Where the assets are under 200 million rupiah. And this business or business is only done at home or looking for a location around housing. Usually this business is called a home business and currently this home business already has various types of products produced. So that businesses that are carried out alone at home are able to support household needs, because the basis for establishing a home business is to meet household needs. This study aims to determine the influence of Product Creativity, Product Variety, and Social Media on Purchase Decisions at Anna Cake N Cookies in Surabaya. This study uses a type of quantitative research. The sample used was 100 respondents who were consumers of Anna Cake N Cookies in Surabaya. Using a non-probability sampling method with a purposive sampling technique. The data collection technique used is by distributing questionnaires online via the Google form. The results of the t test show that the Product Creativity variable has a partial influence on purchasing decisions with the result t count 2.187 > 1.660. The product variation variable has a partial influence on purchasing decisions with the result t count 4.040 > 1.660 . Social Media variables have no partial influence on purchasing decisions with the result t count 0.943 > 1.660. Then the results of the F test show that Product Creativity, Product Variety, and Social Media have a significant simultaneous effect on Purchase Decisions at Anna Cake N Cookies in Surabaya. Keywords: Product Creativity, Product Variety, Social Media, Buying decision